Revascularization in ischaemic heart failure with preserved ejection fraction: a nationwide cohort study. (10th March 2022) - Deo, Salil V.; Reddy, Yogesh N.V.; Zakeri, Rosita; Karnib, Mohamad; Selvaganesan, Padmini; Elgudin, Yakov; Kilic, Ahmet; Rubelowsky, Joseph; Altarabsheh, Salah E.; Osman, Mohammed N.; Josephson, Richard A.; Mohan, Sri Krishna Madan; et al.
Abstract : Aims: Despite the common occurrence of coronary artery disease (CAD) and heart failure (HF) with preserved ejection fraction (HFpEF), there is limited evidence to guide revascularization. Methods and Results: We investigated the long‐term outcomes of coronary artery bypass grafting (CABG) in patients with HF and significant CAD across the spectrum of ejection fraction, using a large national cohort of patients from the Veteran Affairs (VA) Medical Centers in the US. Patients with HF were stratified into groups, HFpEF, HF with mid‐range ejection fraction (HFmrEF), and HF with reduced ejection fraction (HFrEF) and compared to patients with no preoperative HF. We analysed 10 396 patients. Despite an increased hazard in the first year following revascularization, the long‐term survival (median follow‐up 6.6 years; interquartile range 3.7–10.1) of HFpEF post‐CABG was similar to controls (hazard ratio 0.85, 95% confidence interval 0.68‐1.06), but survival progressively declined with HFmrEF and HFrEF. Similar trends were seen with recurrent HF hospitalization with lower risk with baseline HFpEF (43.9 ± 6.9/100 patient‐years) compared to HFmrEF (65.9 ± 3.8/100 patient‐years) and HFrEF (93.4 ± 4.8/100 patient‐years). Although HFpEF patients had lower mortality and HF hospitalization post‐CABG compared to patients with a lower ejection fraction, they experienced the highest rates of future myocardial infarction. Conclusion: Although HFpEF patients with CAD have greater short‐term risk post‐CABG, their long‐term survival is comparable to controls. However, they are at increased risk for HF hospitalizations and myocardial infarction. These data support the safety of CABG in HFpEF patients and suggest continuum of mortality risk for ischaemic HF when stratified by baseline ejection fraction before revascularization. Abstract : Outcomes following coronary artery bypass grafting stratified by heart failure (HF) phenotypes. HFmrEF, heart failure with mid‐range ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction.